DRAMATURGI PENGGUNA AKUN PSEUDONIM (CYBER ACCOUNT) DI TWITTER - Dwika Fajri Rahma Giyoli (2021)
This study uses dramaturgy approach to examine the impression management done by Cyber Account users on Twitter, either on their front stage and back stage. The research data were obtained through observation, documentation and interviews conducted by both the front stage and back stage of seven Cyber Account users. The research findings showed that Cyber Account users have their own self-image that becomes their reference in managing the impressions on Twitter that includes the real self and ideal self of each users. The impression management that occurs on the front stage is done by associating their personal front and setting along with things that are appropriate and supporting the image they want to present, such as the use of photos that represent their image, the style of their tweets and their interaction with followers that are tailored to their respective images. The setting is also needed to supports the atmosphere where they rely on pseudonimity for the accounts they use.